德国齿形链与链轮工业标准分析 - 王秀 (Jixie chuandong)
Based on the analysis of Deutsche silent chain and sprocket industrie standard DIN 8190 —1988 and DIN 8191—1998,the basic principle and methods of design for silent chain,sprockets and generating tools are expatiated,the reference of design and application is provided.